The effective public manager achieving success in government organizations - Cohen, Steven, 1953 September 6- (Jossey-Bass, 2013)
"Revised and updated, this important resource offers highly-accessible coverage of the fundamentals of leading and managing public organizations. All of the key areas of the field are covered and thoughtfully explored through the strategic use of new case studies and real-world examples that are based on recent developments in the sector. The book's new material addresses emerging trends including; the influence of social and mobile technology on management, multi-sectoral public service delivery, innovation and cross-sector collaboration, environmental sustainability, national security and current thinking regarding accountability, transparency and crisis communication"--